Avant-gardes diasporiques et émergence du « tiers espace » : Banjo de Claude McKay et Les Contrebandiers d’Oser Warszawski - Laëtitia Tordjman (Itinéraires)
Studies of the avant-gardes have experienced a kind of “spatial turn” in the past few years, distancing themselves from the traditional dichotomy between centers and peripheries. Avant-gardes are now being understood as transnational and transcultural phenomena. Looking into the avant-garde movements from the point of view of its diasporic elements is to dive into the core of global modernity. The comparative analysis of Jamaican-born writer Claude McKay and Polish Yiddish-speaking writer Oser Warszawski strikingly reveals the same desire to create a new space in their works of fiction—a“third-space” or an “in-between space” (E. Soja, H. Bhabha)—where the racial, national, social, religious and linguistic borders could all be transgressed. During the inter-war period, facing the increase of racial and religious violence, they both try to find their own global literary space and “to conquer the right to tell their story of the world” (É. Glissant).